Complete Genome Sequence of the Grouper Iridovirus and Comparison of Genomic Organization with Those of Other Iridoviruses - Tsai, Chih-Tung (American Society for Microbiology, 2005)
The complete DNA sequence of grouper iridovirus (GIV) was determined using a whole-genome shotgun approach on virion DNA. The circular form genome was 139,793 bp in length with a 49% G+C content. It contained 120 predicted open reading frames (ORFs) with coding capacities ranging from 62 to 1,268 amino acids. A total of 21% (25 of 120) of GIV ORFs are conserved in the other five sequenced iridovirus genomes, including DNA replication, transcription, nucleotide metabolism, protein modification, viral structure, and virus-host interaction genes. The whole-genome nucleotide pairwise comparison showed that GIV virus was partially colinear with counterparts of previously sequenced ranaviruses (ATV and TFV). Besides, sequence analysis revealed that GIV possesses several unique features which are different from those of other complete sequenced iridovirus genomes: (i) GIV is the first ranavirus-like virus which has been sequenced completely and which infects fish other than amphibians, (ii) GIV is the only vertebrate iridovirus without CpG sequence methylation and lacking DNA methyltransferase, (iii) GIV contains a purine nucleoside phosphorylase gene which is not found in other iridoviruses or in any other viruses, (iv) GIV contains 17 sets of repeat sequence, with basic unit sizes ranging from 9 to 63 bp, dispersed throughout the whole genome. These distinctive features of GIV further extend our understanding of molecular events taking place between ranavirus and its hosts and the iridovirus evolution.